Entrepreneurs in the eyes of society – on the causes of negative perception of entrepreneurs in transitional Serbia - Vesna Trifunović (University of Belgrade, 2016)
The paper deals with the negative social perceptions of entrepreneurs often encountered during the second phase of post-socialist transformation in Serbia. The causes of these widespread social perceptions are investigated by contrasting the previous, decades long socialist system, which was hostile toward entrepreneurship as well as egalitarian ideology with the context of the occurrence and development of private enterprise and the relationship between entrepreneurs – employers and workers in this society.